Metabolic plasticity and adaptive evolution in Fragaria vesca: bridging wild diversity to crop improvement - Pérez-Martín, José E.; Bonte, Dries; Osorio, Sonia; Posé, David (Frontiers in Plant Science, 2026)
Plants resilience capacity to environmental variability involves both phenotypic plasticity and genetic differentiation through evolutionary selection. Metabolism, particularly primary metabolism, plays a central role in the plant-environment interface, translating environmental and genetic signals into physiological, developmental, morphological and life history responses. The woodland strawberry, Fragaria vesca, serves as an ideal model system for studying these integrated processes due to its wide ecological distribution, high natural variation, sequenced diploid genome, and experimental tractability. This has resulted in a growing interest in integrating approaches from ecophysiology, metabolomics, and genomics to dissect these complex interactions. This review presents current knowledge on how adaptive phenotypic plasticity and genetic variation contribute to environmental adaptation in plants, with a particular focus on F. vesca, discussing insights from studies examining plasticity along environmental gradients and from metabolomic genome-wide association studies (mGWAS), which integrate metabolomic profiling with GWAS to identify genetic loci underlying metabolite variation and metabolic pathway diversity. This integrative understanding provides a roadmap for leveraging wild genetic resources to enhance crop resilience in changing environments.